A critical analysis of isolation of Paracoccidioides brasiliensis from soil - Franco, Marcello; Bagagli, E. [UNESP]; Scapolio, S. [UNESP]; Da Silva Lacaz, C. (Oxford University Press (OUP), 2000)
The present review is a critical analysis of positive and negative reports of the isolation of Paracoccidioides brasiliensis from soil. The strains isolated from soil or soil-contaminated material (dogfood, penguin feces) by Batista et al. in Recife, Brazil, Negroni in the Argentinian Chaco, Albornoz in rural Venezuela, Silva-Vergara et al. in Ibia, Brazil, Ferreira et al. in Uberlandia, Brazil, and Gezuele et al. at the Uruguayan base in the Antarctic region, presented mycological characteristics consistent with P. brasiliensis. In most of these studies, morphological characterization was complemented with an evaluation of virulence and antigenicity, and biochemical or molecular analysis. These isolations, therefore, can be considered true, supporting the concept of soil as an important element in the ecology of the pathogen. The large number of negative reports in attempts involving soil samples and the low repeatability of isolation of the fungus from the same area indicate that the specific conditions supporting growth of the pathogen in soil have not been fully clarified.
Keywords: Ecology; Paracoccidioides brasiliensis; Paracoccidioidomycosis; Soil